THE IMPACT OF THE COVID-19 PANDEMIC ON STUDENTS BEHAVIOUR DURING ONLINE LEARNING AT PELANGI KASIH ELEMENTARY SCHOOL IN JAKARTAv - Meriana, Tju; Angelius Domes, Angelius; -, Yanna; Sihotang, Hotmaulina (Advances in Social Sciences Research Journal, 2021)
This study aims to determine the impact of the Covid-19 pandemic on students’ behaviour during online learning. This research was conducted at Pelangi Kasih Elementary School, Jakarta. Respondents were grade 6 students, total of 102 respondents, consisting of 53 girls and 49 boys. The study used is quantitative and exploratory method with an descriptive analisys. The results showed that students behaviours are able to be formed successfully during online learning when teachers and parents communicate authentically more often and work together more cooperatively, and the high unfulfilled needs of interaction among students can affect their psychosocial issues.